Development and implementation of a strategy for early diagnosis and management of scrub typhus: an emerging public health threat - Hitesh Kumar Jain; Arundhuti Das; Sujata Dixit; Harpreet Kaur; Sanghamitra Pati; Manoranjan Ranjit; Ambarish Dutta; Madhusmita Bal (Frontiers in Public Health, 2024)
Scrub typhus, caused by Orientia tsutsugamushi, is a re-emerging zoonotic disease in the tropics with considerable morbidity and mortality rates. This disease, which is mostly prevalent in rural areas, remains underdiagnosed and underreported because of the low index of suspicion and non-specific clinical presentation. Limited access to healthcare, diagnostics, and treatment in rural settings further makes it challenging to distinguish it from other febrile illnesses. While easily treatable, improper treatment leads to severe forms of the disease and even death. As there is no existing public health program to address scrub typhus in India, there is an urgent need to design a program and test its effectiveness for control and management of the disease. With this backdrop, this implementation research protocol has been developed for a trial in few of the endemic “pockets” of Odisha, an eastern Indian state that can be scalable to other endemic areas of the country, if found effective. The main goal of the proposed project is to include scrub typhus as a differential diagnosis of fever cases in every tier of the public health system, starting from the community level to the health system, for the early diagnosis among suspected cases and to ensure that individuals receive complete treatment. The current study aimed to describe the protocol of the proposed Scrub Typhus Control Program (STCP) in detail so that it can receive valuable views from peers which can further strengthen the attempt.